Future changes in boreal winter ENSO teleconnections in a large ensemble of high-resolution climate simulations - Johnson, Nathaniel C.; Wittenberg, Andrew T.; Rosati, Anthony J.; Delworth, Thomas L.; Cooke, William (Frontiers in Climate, 2022)
The impacts of the El Niño-Southern Oscillation (ENSO) are expected to change under increasing greenhouse gas concentrations, but the large internal variability of ENSO and its teleconnections makes it challenging to detect such changes in a single realization of nature. In this study, we explore both the internal variability and radiatively forced changes of boreal wintertime ENSO teleconnection patterns through the analysis of 30-member initial condition ensembles of the Seamless System for Prediction and EArth System Research (SPEAR), a coupled global climate model developed by the NOAA Geophysical Fluid Dynamics Laboratory. We focus on the projected changes of the large-scale circulation, temperature, and precipitation patterns associated with ENSO for 1951-2100 under a high emissions scenario (SSP5-8.5). We determine the time of emergence of these changes from the noise of internal climate variability, by determining by the time when the ensemble mean change in the running 30-year ENSO composites first exceeds the ensemble standard deviation of 1951-1980 composites. Overall, the high internal variability of ENSO teleconnection patterns primarily limits their emergence to tropical and subtropical regions before 2100, where some regions experience robust changes in ENSO-related temperature, precipitation, and 500 hPa geopotential height patterns by the middle of the 21st century. The earliest emergence generally occurs over tropical South America and Southeast Asia, indicating that an enhanced risk of ENSO-related extreme weather in that region could be detected within the next few decades. We further explore the diversity of ENSO teleconnections within the SPEAR large ensemble during the historical period, and demonstrate that historical relationships between tropical sea surface temperatures and ENSO teleconnections are skillful predictors of projected changes in the Northern Hemisphere El Niño 500 hPa geopotential height pattern.